2015
DOI: 10.2319/032015-174.1
|View full text |Cite
|
Sign up to set email alerts
|

Upper airway assessment using four different maxillary expanders in cleft patients: A cone-beam computed tomography study

Abstract: Only the Hyrax and inverted mini-hyrax on the molar expanders effectively increased the nasal passage volume, and none of the expanders evaluated in this study modified the oropharyngeal airway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
0
13
0
2
Order By: Relevance
“…Some previous morphological studies have reported nasal airway enlargement via RME in children with UCLP, but few functional studies of the nasal airways in children with UCLP have been reported. From these morphological studies and the morphological and CFD results of the current study, we conclude that RME improved ventilation of the nasal airway in children with UCLP by enlarging the nasal airway. Furthermore, nasal septum deviation in children with UCLP was reduced at T2.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some previous morphological studies have reported nasal airway enlargement via RME in children with UCLP, but few functional studies of the nasal airways in children with UCLP have been reported. From these morphological studies and the morphological and CFD results of the current study, we conclude that RME improved ventilation of the nasal airway in children with UCLP by enlarging the nasal airway. Furthermore, nasal septum deviation in children with UCLP was reduced at T2.…”
Section: Discussionmentioning
confidence: 98%
“…However, improvements in nasal airway ventilation associated with RME in children with UCLP are unclear, particularly in cases involving nasal airway ventilation obstruction . In studies investigating RME in patients with UCLP, the volume and cross‐sectional area of the nasal airway reportedly increase.…”
Section: Introductionmentioning
confidence: 99%
“…Its effects in increasing the airway volume has been tackled in many studies. 8,10,12 The fan expander has been favored by many orthodontists in treating BCLP patients due to the considerable amount of anterior expansion it has on the dental arch, which is much needed in anteriorly collapsed arches, a common finding in BCLP patients. However, the hyrax expander has almost always been the golden standard of care in constricted maxillae, having excellent results in expanding the arch both posteriorly as well as anteriorly.…”
Section: Discussionmentioning
confidence: 99%
“…Usually this occurs in preparation for the alveolar cleft grafting procedure during the mixed dentition/early permanent dentition stages. The effect of the RME on the nasal chambers were raised with a considerable amount of debate whether the change produced by RME increases the nasal chambers width [9][10][11] , which inevitably will enhance nasal breathing in these individuals, otherwise suffering nasal respiration restriction. Our study's purpose was to assess whether the type of expander would affect the anterior and posterior nasal widths after expanding the maxillary dental arch.…”
Section: Discussionmentioning
confidence: 99%